Relational development locating the stages of a romantic relationship through a textual analysis of an exchange of love letters between a man and a woman in the 1950s - Arce, Julienne Louise A.; Dela Rosa, Jona Siena D.T.; Llanto, Sheila Marie D. (2008)
Interaction determines our roles in certain situations, and our roles in certain situations define what kind of relationships we are in, and how we go about in pursuing relationships. Because relationships are more personal, face to face communication is generally an easier tool to pursue them. This study however proved the importance of communication that is not face to face in the formation of a relationship. Looking at relationships as developmental, the researchers located stages in a relationship that was formed through letter writing, and determined roles that the couple played in the interaction, thus leading from a shallow relationship to one that is secured in marriage.
Thesis (Bachelor of Arts in Communication) -- University of the Philippines Baguio, 2008.
Includes bibliographical references (leaves 98-99)
Keywords: Man-woman relationships -- Philippines; Communication